2019
DOI: 10.23822/eurannaci.1764-1489.101
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic interactions in asthma

Abstract: Metabolomics can be used to explore altered metabolic pathways in asthma, giving insights into its pathophysiology. We aimed to review how metabolomics has been used to understand asthma by describing metabolic pathways under research and discussing clinical implications. The search was performed in PubMed, and studies published since 2000 using a metabolomics approach, were included. A total of 32 studies were analysed. Pathways related with cellular energy homeostasis, lipid metabolism and oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Other metabolites significantly altered in UC patients are arginine, which is related to the nitric oxide (NO) pathway 38,41‐44 ; and leucine, associated with the activation of mTORC1 pathways responsible for T cells activation, proliferation and differentiation 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other metabolites significantly altered in UC patients are arginine, which is related to the nitric oxide (NO) pathway 38,41‐44 ; and leucine, associated with the activation of mTORC1 pathways responsible for T cells activation, proliferation and differentiation 45 …”
Section: Discussionmentioning
confidence: 99%
“…Other metabolites significantly altered in UC patients are arginine, which is related to the nitric oxide (NO) pathway 38,[41][42][43][44] ; and leucine, associated with the activation of mTORC1 pathways responsible for T cells activation, proliferation and differentiation. 45 Furthermore, proteomic analysis reveal that UC patients seems to have an increased pro-inflammatory T cell response, which is also supported but the changes in S1P and leucine abovementioned.…”
Section: Discussionmentioning
confidence: 99%
“…[1,[3][4][5][6] This metabolome, governed by the interaction of a person's genetics with diet, environmental factors, and the gut microbiome, provides the closest representation of the functional phenotype, thus giving insights into metabolic changes in health and disease. [2,[7][8][9] So far, metabolomic fingerprinting has emerged as a powerful technique to uncover biologically relevant biomarkers and pathway alterations, contributing to a variety of complex diseases, including obesity, diabetes, inflammatory bowel diseases, and a variety of cancers. [3,[10][11][12][13] In this regard, the analysis of the metabolome provides unprecedented opportunities in the quest for biomarkers of IgE-mediated allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, metabolomics can discriminate between healthy individuals and patients with bronchial asthma. Globally, the most frequently identified metabolites, although with differences across studies, have involved energy homeostasis, lipid metabolism, tricarboxylic acid cycle, oxidative stress, hypoxia-associated molecules and various metabolites associated with immunoinflammatory processes that may be relevant to the underlying immunopathology of asthma [ 49 , 93 , 94 ]. Most of these affected metabolic pathways are concordant with the fact that asthma is a chronic, inflammatory disease, which requires changes in energy supply and possibly also metabolic reprogramming, namely in immune cells involved in the process.…”
Section: Main Metabolomic Signatures and Their Potential Implications In Adult Asthmamentioning
confidence: 99%
“…The reproducibility of metabolomics signatures in asthma may also be checked by comparing results between children and adult studies, since finding similar results will strengthen the possible relevance of detected changes. In fact, several studies in children and in adults have coincided in the main metabolites, at least regarding discrimination between asthma and a healthy state [ 32 , 64 , 88 , 92 , 94 ]. However, comparative studies regarding the capacity to discriminate between asthma inflammatory and/or clinical phenotypes are necessary, although the previously mentioned study by Abdel-Aziz [ 113 ], which showed the capacity of eNose metabolomics in exhaled breath to predict an atopic asthma phenotype in adults and children, is a good example of reproducibility.…”
Section: Reproducibility and Stability Of Asthma-related Metabolic Signatures: Of Validation Cohorts Time Stability Age Sex And Other Facmentioning
confidence: 99%